Price Smoothing Behavior of Cigarette Firms in Indonesia - Putra, Amin Dwinta; Adrison, Vid (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This research analyzes the price-smoothing behaviors of cigarette firms across various cigarette types, firm classifications, and government policies by using quarterly data at the brand level.Research Objectives: This research aims to identify the price-smoothing tendencies of cigarette firms in Indonesia by analyzing the change in market retail price across various cigarette types and firm classifications and the impact of government policies.Research Methods: This research used quarterly market retail price survey data covering all cigarette brands available in Indonesia from March 2014 to June 2021. The System Generalized Method of Moments (System GMM) was identified as the optimal estimation method.Empirical Results: The results showed that cigarette firms in Indonesia employed price-smoothing strategies in response to implementing the tariff increase policy. Notably, substantial price increases tend to occur in December, immediately following the announcement of the tariff increase policy. Removing one of the ceiling price criteria has led to an increase in the average price of cigarettes within the specified criteria. The implementation of a minimum price had no significant impact on price changes.Implications: This study's findings suggest that to address the issue of rising smoking prevalence, the government should consider implementing a more substantial tariff increase to counteract the impact of price-smoothing.JEL Classification: H24, H31, H32, I18